2019
DOI: 10.1016/j.ijppaw.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and muscle distribution of Trichinella britovi in raccoon dogs (Nyctereutes procyonoides) in wildlife in the Głęboki Bród Forest District, Poland

Abstract: The raccoon dog ( Nyctereutes procyonoides ) is an introduced, invasive species in Europe. Literature data show that raccoon dogs act as a reservoir of many dangerous parasites, including nematodes of the genus Trichinella . The aims of the study were to determine the prevalence of Trichinella spp. infection in raccoon dogs collected from the Głęboki Bród Forest District between 2013 and 2016, and to evaluate their distribution in the muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The Western European country that had the largest number of literature available was Spain (13 articles), but few of these works were published recently (Díaz et al., 2021; Rodríguez‐Rodríguez et al., 2015). In central Europe, Italy had the most publications, with 10 articles (Badagliacca et al., 2016; Bandino et al., 2015; Marucci et al., 2021; Pozio et al., 2021; Ricchiuti et al., 2021), while in Eastern Europe, Poland had the largest number of studies, a number of which were published recently (Bień et al., 2016; Bilska‐Zając et al., 2016, 2017, 2020; Cybulska et al., 2016, 2019, 2020; Flis et al., 2017; Hurníková et al., 2016; Różycki et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The Western European country that had the largest number of literature available was Spain (13 articles), but few of these works were published recently (Díaz et al., 2021; Rodríguez‐Rodríguez et al., 2015). In central Europe, Italy had the most publications, with 10 articles (Badagliacca et al., 2016; Bandino et al., 2015; Marucci et al., 2021; Pozio et al., 2021; Ricchiuti et al., 2021), while in Eastern Europe, Poland had the largest number of studies, a number of which were published recently (Bień et al., 2016; Bilska‐Zając et al., 2016, 2017, 2020; Cybulska et al., 2016, 2019, 2020; Flis et al., 2017; Hurníková et al., 2016; Różycki et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Trichinella britovi is widely distributed among wildlife and several studies have con rmed that this species predominates in red foxes, raccoon dogs and wolves in Poland [10,[19][20][21]. The parasite was also found in martens and badgers living the north-east regions of Poland, which only proves its circulation in a wide range of hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Trichinella britovi is widely distributed among wildlife and several studies have confirmed that this species predominates in red foxes, raccoon dogs, and wolves in Poland [ 9 , 22 , 23 , 24 ]. The parasite has also been found in martens and badgers living in the northeast regions of this country [ 25 ], which only proves its circulation in a wide range of hosts.…”
Section: Discussionmentioning
confidence: 99%